Ecological features of exotic Vespula wasps (Hymenoptera: Vespidae) invading the southernmost UNESCO Biosphere Reserve - Rendoll-Carcamo, Javier; Convey, Peter; Ganan, Melisa; Maldonado-Marquez, Alan; Zuniga, Luna Menares; Contador Mejias, Tamara Andrea (My University, 2022)
Invasive alien species may cause substantial changes and damaging impacts. Here, we document the current distribution and ecological interactions with native biota of relatively recently introduced wasps, Vespula vulgaris and V. germanica, in the southern part of the Cape Horn Biosphere Reserve (CHBR) in southern Chile. We conducted field studies in four different habitats on Navarino Island: evergreen, deciduous and mixed forests, and shrublands. The spread of V. vulgaris throughout the island has led to it occupying suitable habitats in both urban and rural settings, while V. germanica has not been observed in the last 2 years. The presence of V. vulgaris in remote areas of the CHBR is likely the result of human-mediated movement through the channels within the reserve. The composition of foraged items was different in each of the four studied habitats, yet strongly linked to the resources of each, indicating the inherent ability of V. vulgaris to exploit available resources efficiently. V. vulgaris mainly forages berries from shrubs, and preys on a variety of arthropods, particularly hoverflies, craneflies and lepidoptera larvae. The lack of natural competitors and availability of multiple resources has allowed V. vulgaris to rapidly become a common pest in urban and rural settings in the southern extremity of South America. While we consider that eradication would now be impossible, population control at local scales may still be possible with proper planning and long-term management. Our data provide a baseline for management planning, and we strongly recommend social engagement and dialog with relevant governmental institutions to achieve this challenging task.
Keywords: biosphere reserve; non-native; invasive species; sub-antarctic; vespula vulgaris; vespula germanica